1995
DOI: 10.1063/1.359898
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of thermal grooving for arbitrary grain-boundary flux

Abstract: Groove profiles are computed under isotropic conditions for the intersection of a periodic array of grain boundaries with an external surface, assuming that grain boundary flux I is directed to (I≳0) or away from (I<0) the surface. When I=0, the surface assumes an equilibrium (time-independent) profile. For I≠0, in a range bounded by upper and lower limits that depend on geometry and material parameters, a global steady-state develops in which the entire surface advances (I≳0) or recedes (I<0) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…How is this morphology affected by changes in the In the present simulations, the elastic strain energy density contribution is ignored since the elastic dipole interaction term is at least a few orders of magnitude larger than the ESED term, especially for the medium stress levels [22]. This may be seen from the following calculated figures using the values tabulated in Table 1 [1][2][3][4][5][6][7][8][9][10] assigned previously for EDTI. However, as mentioned previously, the difference between these two parameters decreases as the stress levels increase.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…How is this morphology affected by changes in the In the present simulations, the elastic strain energy density contribution is ignored since the elastic dipole interaction term is at least a few orders of magnitude larger than the ESED term, especially for the medium stress levels [22]. This may be seen from the following calculated figures using the values tabulated in Table 1 [1][2][3][4][5][6][7][8][9][10] assigned previously for EDTI. However, as mentioned previously, the difference between these two parameters decreases as the stress levels increase.…”
Section: Resultsmentioning
confidence: 94%
“…(2) At sufficiently large magnitudes of the GBF, the GB roots break away from the remaining surface to form rapidly growing ridges or slits. Klinger et al [7] stated that the use of small slope assumption (SSA) hinders the transition between these two modes; thus, a global steady-state is always possible from the solution of linearised equation. Under the SSA, Rosenberg and Ohring [8] and Genin et al [9] treated isolated groove development with constant GBF as being due to electromigration forces and normal stress gradients, respectively, acting on the grain boundary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grain size of a film is closely related to its thickness because of the influence of the substrate or other underlying layers. [12][13][14] The crystallographic orientation of the film is also highly influenced by its thickness because the total strain energy stored in the system is proportional to the thickness of the film. 9,10 In addition, the orientation as well as the microstructure of the film is strongly influenced by the characteristics of the underlying layer.…”
Section: Introductionmentioning
confidence: 99%
“…Chuang and Rice (1973) showed that a slit-like cavity may extend on a grain boundary if mass diffuses rapidly into the boundary ahead of the tip. Thouless (1993) and Klinger et al (1995) studied slit formation on parallel grain boundaries. The co-evolution of pores and grains during sintering sets the microstructure of a final product.…”
Section: Surface Invariant In One Directionmentioning
confidence: 99%